FITUR-FITUR BAHASA PEREMPUAN YANG DIGUNAKAN OLEH BTS ARMY DALAM WHATSAPS GROUPCHAT BUTTER ARMY OF INDONESIA - Melina Anggraini (Translation and Linguistics (Transling), 2024)
Abstract:  The use of woman language against the background of K-POP fans, especially the boy group BTS, is very interesting to discuss. This research focuses on analyzing the features of woman language used by BTS fans called ARMY in whatsaap group chat Butter ARMY of Indonesia. This research uses a qualitative descriptive method by applying a sociolinguistic approach that focuses on the use of woman language features in whatsapp group chat Butter ARMY of Indonesia. The data collection technique was carried out using the technique of listening and recording through orthographic transcription. This research uses a method as a pragmatic commensurate data analysis with the determining tool is the speech partner itself based on the speaker's language. The basic technique applied is the sorting of determining elements (PUP). Based on the results of the study, it was found that the use of Women's Language features in the whatsaap group chat Butter ARMY of Indonesia was 70 data where the use of Question tag features was more dominant as many as 19 and the use of Rising Intonation on Declaration was the least used which was only 1 data.